Preparation and Characterization of Floating Tablets of Venlafaxine Hydrochloride: An Approach for Depression Treatment - Kumar, Sachin (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The present work is to formulate floating tablets of venlafaxine hydrochloride as this drug is used to treat depression. Gastrointestinal tract absorption of venlafaxine hydrochloride is poor due to low aqueous solubility. Thus, an attempt was made to enhance it gastric residence time that will improve its dissolution profile. Materials and Methods: The floating tablets were prepared by direct compression method using HPMC K100M and Pullulan gum as polymer in different combinations. Sodium bicarbonate and citric acid are added to cause effervescence. The floating tablets were evaluated for hardness, thickness, friability, swelling index, and drug content. Results: The Fourier transform-infrared spectroscopy revealed the absence of any drug-polymer interactions. The drug content of tablets was in the range of 97.43 ± 1.56–98.71 ± 2.87%. The floating lag times of tablets for all batches were found in the range of 36.0 ± 1.1–68.0 ± 2.9 s. The drug release from floating tablets followed Korsmeyer-Peppas model. Discussion and Conclusion: The results suggested that prepared floating tablets containing venlafaxine hydrochloride could enhance gastric residence time as remain buyout for long time and modulate the drug release.